ECOLOGICAL CONDITION OF IRRIGATED LANDS IN DO‘STLIK DISTRICT, JIZZAKH REGION - Safarov Anvar Abdinazarovich (European Science Publishing, 2024)
This article presents information on the ecological condition of soils based on the results of research on the impact of anthropogenic and natural factors on irrigated lands in Do‘stlik District, Jizzakh Region.
Keywords: Irrigated lands, anthropogenic, natural, factor, ecological condition, soil fertility, agriculture, food products, productivity.